Dynamic behavior of a piezowalker, inertial and frictional configurations - MARIOTTO, GUIDO; SHVETS, IGOR (American Institute of Physics, 1999)
We have examined two configurations of a piezowalker, the inertial and the frictional one, both of which are capable of moving samples with submicrometer steps over a distance of some millimeters. We demonstrated that, contrary to expectations, operation of the frictional walker in which six piezos shear one by one, is still dependent on inertial slip-stick action. We studied the dependence of the step size on the time delay between rising fronts applied to consecutive piezos and we found that the characteristic time associated with the minimum value of the step size is of the order of the time of a sound wave propagating along the rod between the piezos
PUBLISHED
Keywords: Atomic, molecular and chemical physics; piezowalker